ANALISIS TEKS BERITA YANG DITULIS SISWA PADA MASA DARURAT COVID-19 DI KELAS VIII SMP NEGERI 3 SILAT HILIR - Marta Marimar; Abdussamad Abdussamad; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstrakThis study aims to describe the quality of news text writing during the Covid-19 emergency in class VIII of SMP Negeri 3 Silat Hilir. This study describes the writing of news texts during the Covid-19 period in terms of content aspects, structural aspects, and linguistics.The method used in this research is descriptive qualitative. The object of this research is students of class VIII A at SMP Negeri 3 Silat Hilir. The object of research focuses on the quality of students' writing on news text learning. The type of data used is qualitative in the form of a description of the observations. Data obtained through teachers and personal notes in the form of documents.Based on the results of the analysis and discussion, it can be concluded that the writing quality of the students of SMP Negeri 3 Silat Hilir in terms of content and structure is in accordance with the content of the news text. Meanwhile, for the linguistic aspect, the students of SMP Negeri 3 Silat Hilir are categorized as still less able to write news texts. Constraints or obstacles faced by students of SMP Negeri 3 Silat Hilir in writing news texts, especially in class VIII A, are the lack of material taught by the teacher, the non-existent internet network, the lack of facilities owned by students in participating in face-to-face learning is limited.Keywords: Analysis, Writing, News Text